2010
DOI: 10.1038/onc.2010.222
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitous nature of cancer: the role of the SCFFbw7 complex in development and transformation

Abstract: The ubiquitin-proteasome system (UPS) is a multi-subunit pathway that allows for ubiquitin modification of proteins and leads to either degradation or other non-proteolytic processes such as trafficking or transcriptional activation. Given its role as a regulator of cellular homeostasis it is not surprising that members of the UPS are frequently aberrantly expressed in a number of disease states including cancer. This review will focus on one member of the UPS, the F-box protein, Fbw7 (also known as Sel-10, Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 78 publications
0
104
0
Order By: Relevance
“…The deregulation of the UPS has been observed in many types of cancer, and studies targeting the UPS for cancer therapy are being conducted (27). As a component of the UPS, Fbw7 ubiquitin ligase plays a vital role in cell fate decisions (35,42). It was recently shown that Fbw7 controlled the fate of hematopoietic stem cells (43) and affected the proliferation and lymphomagenesis of mouse T cells (44), both through the regulation of c-Myc expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deregulation of the UPS has been observed in many types of cancer, and studies targeting the UPS for cancer therapy are being conducted (27). As a component of the UPS, Fbw7 ubiquitin ligase plays a vital role in cell fate decisions (35,42). It was recently shown that Fbw7 controlled the fate of hematopoietic stem cells (43) and affected the proliferation and lymphomagenesis of mouse T cells (44), both through the regulation of c-Myc expression.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that the GSK-3-mediated phosphorylation of c-Myc T58 was needed for the efficient binding of c-Myc by Fbw7 (34,35). We investigated GSK-3 activity in K562 cells upon oridonin treatment.…”
Section: Oridonin Activates Gsk-3 and Enhances The Phosphorylation Ofmentioning
confidence: 99%
“…The loss and mutation of this gene is frequently detected in various types of cancers (Mao et al, 2004;Perez-Losada et al, 2005;Tan et al, 2008;Crusio et al, 2010). To address whether downregulation of Fbxw7 mimicked the effects from increase of miR-27a expression, we introduced specific siRNAs duplex targeting Fbxw7 into HBER cells.…”
Section: The Fbxw7 Gene Is a Direct Target Of Mir-27amentioning
confidence: 99%
“…The regulation of KLF2 mRNA expression has been well studied in the endothelium [16]. Accumulating evidence shows that MEF2 transcription factors are the central regulators of KLF2 mRNA expression in endothelial cells.…”
Section: Introductionmentioning
confidence: 99%